Repeated vaccination against Haemonchus contortus provides continuous protection to young grazing sheep - Bassetto, Cesar C. [UNESP]; Almeida, Fabiana A. [UNESP]; Newlands, George F.J.; Smith, W. David; Amarante, Alessandro F.T. [UNESP] (Elsevier, 2020)
Haemonchus contortus is the most important gastrointestinal nematode in the tropics and subtropics causing huge economic losses to the small ruminant industry. Vaccination is potentially a sustainable approach to control this parasite and the performance of Barbervax® a vaccine containing integral membrane glycoproteins from H. contortus intestinal cells, was evaluated in naturally infected grazing sheep during their development from sucking lambs to adults. The sheep were randomly assigned to two groups: Vaccine and Control. The Vaccine group were vaccinated 23 times over the course of this two-year trial at intervals of 3–6 weeks. They responded with anti-vaccine specific antibodies, had 80 % lower Haemonchus egg counts and were less anaemic compared with the controls. Packed cell volumes (PCV) were always greater than 25 % in the vaccinated sheep but averaged between 23 % and 24 % in the controls. Total plasma protein values were higher in the vaccinated group from the third vaccination until the end of the trial. Throughout the trial, 88 % of the control sheep were drenched (average of 3.1 drenches per treated animal) but only 57 % of vaccinates, needed a salvage anthelmintic treatment (average of 1.9 drenches per treated animal), however, between group no differences in body weight were observed. In summary, these results indicate that a continuous course of Barbervax® can provide lambs with substantial year-round protection against H. contortus until they reached adulthood.
Keywords: Barbervax®; Haemonchosis; Parasitic gastroenteritis; Prophylaxis; Sheep